Flexible design of building integrated thin‐film photovoltaics. (1st May 2022) - Neugebohrn, Nils; Haas, Stefan; Gerber, Andreas; Grimm, Michael; Nissel, Jana; Liebers, Rene; Turan, Bugra; Gehrke, Kai; Vehse, Martin
Abstract: The high cost of building integrated photovoltaics is one of the main reasons preventing a more widespread application. We propose a panel‐on‐demand concept for flexible design of building integrated thin‐film photovoltaics to address this issue. The concept is based on the use of semi‐finished PV modules (standard mass products) with subsequent refinement into BIPV PV modules. In this study, we demonstrate the three processes necessary to realize this concept. First, a prototype tool to cut thin film photovoltaic elements on glass substrates based on laser perforation was developed. Damage to the processed samples did not exceed a distance of 50 μm from laser cuts. Second, oxide/metal/oxide‐electrodes with integrated colour were applied on Cu (In, Ga)Se2 cells and standard monolithic interconnection structuring was used to produce modules sized 30 × 30 cm 2 in red, green and blue with strong colours. Third, A back‐end interconnection process was developed for amorphous silicon thin film cells, which allows for the structuring of modules from elements of custom shape. The panel‐on‐demand strategy may allow for a streamlined production of customized modules and a lower cost for aesthetically pleasing, fully building integrated solar modules. Abstract : The high cost of building integrated photovoltaics is one of the main reasons preventing a more widespread application. We propose a panel‐on‐demand concept for flexible design of building integrated thin‐film photovoltaics to address this issue. In this study, we report on the technologies necessary to realize the concept for thin film photovoltaics, namely, laser‐based cutting of semi‐fabricates, a front contact electrode with integrated colours, and a back‐end interconnection process for the cell‐to‐module production step.